Is playing string or wind musical instruments a risk factor for temporomandibular dysfunction? A Systematic Review. - Leite Cavalcanti, Alessandro (Journal of Oral Research, 2019)
Aim. Medical problems specifically affecting professional musicians are commonly mentioned in the literature. The present study is aimed to evaluate, through a systematic review, the possible association between the practice of string with bow and wind musical instruments and the occurrence of Temporomandibular Dysfunction (TMD). Methods. The search for articles was conducted in PubMed/Medline, Web of Science, Scopus, Lilacs, Cochrane Library, and Open Gray databases, and there was no restriction on language or date of publication. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. The MeSH terms used were: “music”; “temporomandibular joint”; “temporomandibular joint disorders”; “temporomandibular joint dysfunction syndrome”; and “occupational diseases”. Cross-sectional studies, case-control, cohort and clinical trials were included that involved the practice of string with bow and wind musical instruments and the occurrence of Temporomandibular Dysfunction (TMD). Articles were previously selected by title and abstract. Qualitative evaluation was done through the Newcastle-Ottawa Scale. Results. The literature search identified 732 studies, of which 10 met the inclusion criteria, nine of them cross-sectional studies and one a clinical intervention study. The TMD prevalence ranged from 47.0% to 89.0%. Recruitment of participants took place in professional schools and orchestras, and in bands of professional musicians. All studies reported associations between TMD and the practice of musical instruments, and violinists presented higher prevalence rates when compared to other instrument groups.